Development of a sensory lexicon and sensory wheel for rooibos (Aspalathus linearis) and the role of its phenolic composition on taste and mouthfeel. - Koch, Ilona Sabine (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc Food Sc)--University of Stellenbosch, 2011.